Denosumab for Prevention of Acute Onset Immobilization‐Induced Alterations of Bone Turnover: A Randomized Controlled Trial. (23rd September 2022) - Wadiura, Lisa Irina; Butylina, Maria; Reinprecht, Andrea; Aretin, Marie‐Bernadette; Mischkulnig, Mario; Gleiss, Andreas; Pietschmann, Peter; Kerschan‐Schindl, Katharina
ABSTRACT: Metabolic bone disease is a devastating condition in critically ill patients admitted to an intensive care unit (ICU). We investigated the effects of early administration of the antiresorptive drug denosumab on bone metabolism in previously healthy patients. Fourteen patients with severe intracerebral or subarachnoid hemorrhage were included in a phase 2 trial. Within 72 hours after ICU admission, they were randomized in a 1:1 ratio to receive denosumab 60 mg or placebo subcutaneously. The primary endpoint was group differences in the percentage change of C‐terminal telopeptide of type 1 collagen (CTX‐1) levels in serum from denosumab/placebo application to 4 weeks thereafter. Changes in serum levels of bone formation markers and urinary calcium excretion were secondary outcome parameters. Regarding serum levels of CTX‐1, changes over time averaged −0.45 ng/mL (95% confidence interval [CI] −0.72, −0.18) for the denosumab group and 0.29 ng/mL (95% CI −0.01, 0.58) for the placebo group. The primary endpoint, the group difference in changes between baseline and secondary measurement, adjusted for baseline serum levels and baseline neurological status, averaged −0.74 ng/mL (95% CI −1.14, −0.34; p = 0.002). The group difference in changes between baseline and secondary osteocalcin measurement averaged −5.60 ng/mL (95% CI −11.2, −0.04; p = 0.049). The group difference in averaged change between baseline and secondary measurement of 24‐hour urine calcium excretion was significant (−1.77 mmol/L [95% CI −3.48, −0.06; p = 0.044]). No adverse events could be attributed to the study medication. The investigation proved that a single application of denosumab early after admission to an ICU prevents acute immobilization‐associated increase in bone resorption among previously healthy individuals. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).